KEBERAGAMAN BENTUK LAHAN DI DAERAH TUKSONGO DAN SEKITARNYA, KECAMATAN BOROBUDUR, KABUPATEN MAGELANG, JAWA TENGAH KAITANNYA DENGAN KARAKTERISTIK GEOMORFOLOGI - Amri, Muhammad Adimas (JURNAL GEOGRAFI, 2024)
The research area is located in the Tuksongo area and its surroundings, Borbudur District, Magelang Regency, Central Java. Astronomically, the area is 110°10'21.8"– 110° 13' 39.0" East Longitude and 7°36'36.4"– 7° 38' 20.2" South Latitude. With an area of 30 km2, the mapping area has its own charm, especially from a geomorphological perspective. All geological aspects in the mapping area are closely related to intensive volcanic activity in the Oligocene to Miocene which was controlled by 3 ancient volcanoes, namely Mount Ijo, Mount Gajah and Mount Menoreh. Apart from that, recent volcanic activity such as Mount Sumbing also plays a role in forming the mapping area. Geomorphologically, in the mapping area there are four units, namely the Kerukbatur Lava Flow Ridge Geomorphological Unit, the Ngaglik Caldera Wall Geomorphological Unit, the Bejen Pyroclastic Flow Plain Geomorphological Unit and the Tuksongo Alluvial Plain Geomorphological Unit.